Mapping the State of the Art of ESP32-Based Robotics for STEM Physics Education - Thufail Mujaddid Al-Qoyyim; Satutik Rahayu; Erin Ryantin Gunawan (Experiment: Journal of Science Education, 2026)
The rapid development of Industry 4.0 has driven increased the demand for physics education that fostes science process skills and problem-solving abilities through technology-integrated learning. This study surveys the current state of ESP32-based educational robotics integrated with STEM approaches in physics education and identifies research gaps. A systematic review was conducted on publications from 2020 to 2025 in reputable databases, including Scopus, Springer, IEEE Xplore, MDPI, and Taylor Francis. Bibliometric analysis using VOSviewer examined research trends, thematic patterns, and emerging topics. Results reveal a surge in studies on STEM, educational robotics, and IoT, though most focus on general learning outcomes, motivation, or conceptual frameworks. Few studies explicitly design ESP32-based robotic tools as experimental resources to support quantitative physics inquiry and science process skills. This review emphasizes the need for structured ESP32-based robotics combined with STEM and project-based learning to improve data-driven physics experiments. The results offer a conceptual foundation for future research in STEM-based physics learning media.